2012 38th IEEE Photovoltaic Specialists Conference 2012
DOI: 10.1109/pvsc.2012.6318172
|View full text |Cite
|
Sign up to set email alerts
|

Strain effects on radiation tolerance of quantum dot solar cells

Abstract: A comparison of quantum dot (QD) triple junction solar cells (TJSCs) under tensile strain are compared to those under compressive strain and baseline devices to examine the effects of strain induced by the QD layers. It is found that tensile strain leads to degradation of i-region material at values of -706 ppm. Irradiating with 1 MeV electrons triple junction solar cells with tensile strain exhibit a faster degradation in Ise of the QD samples and slower degradation in Voc but overall faster degradation in ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…QDs are, thus desirably used to absorb specific parts of the solar spectrum within solar cells. In addition, they exhibit radiation tolerance as compared to their bulk counterpart, making them more suitable for space applications [2], [3]. More importantly, semiconductor QD solar cells (QDSCs) have the prerequisites for several proposed concepts for third generation photovoltaic, such as hot carrier [4], multi-exciton generation [5], and especially intermediate band solar cells (IBSC) [6], [7] which has an overwhelming theoretical efficiency of 63%.…”
Section: Introductionmentioning
confidence: 99%
“…QDs are, thus desirably used to absorb specific parts of the solar spectrum within solar cells. In addition, they exhibit radiation tolerance as compared to their bulk counterpart, making them more suitable for space applications [2], [3]. More importantly, semiconductor QD solar cells (QDSCs) have the prerequisites for several proposed concepts for third generation photovoltaic, such as hot carrier [4], multi-exciton generation [5], and especially intermediate band solar cells (IBSC) [6], [7] which has an overwhelming theoretical efficiency of 63%.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the ultimate goal of the present research is to analyze the possible use of the MQWs to enhance the MJ performance at both beginning of life (BOL), i.e., prior to radiation, and end of life (EOL), i.e., after radiation. Previous publications have shown that the radiation response of an MQW solar cell can vary significantly, depending on the specific solar cell design [3], [6]- [13]. The external quantum efficiency (EQE) at wavelengths associated with the MQW region, i.e., at wavelengths longer than the bandgap of the bulk material, has been reported to be relatively insensitive to radiation.…”
mentioning
confidence: 99%